Edukasi Penguatan Wawasan Kebangsaan Bagi Mahasiswa Melalui Nilai-Nilai Pancasila - Suhendra Suhendra; Faila Sufa Marhamah; Bambang Suprianto (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2024)
This study explores the implementation of national insight enhancement for students through the integration of Pancasila values into education. The focus is on fostering a profound understanding of the nation's identity and values among students. By incorporating Pancasila principles into the educational framework, this research aims to contribute to the development of well-rounded individuals who possess a strong sense of national consciousness. The study employs various educational strategies to engage students in critical thinking and reflection, fostering a holistic approach to citizenship. Through this initiative, it is anticipated that students will emerge as active participants in shaping the nation's future, grounded in the principles of Pancasila.